An early modern human from the Peştera cu Oase, Romania - Trinkaus, Erik (National Academy of Sciences, 2003)
The 2002 discovery of a robust modern human mandible in the Peştera cu Oase, southwestern Romania, provides evidence of early modern humans in the lower Danubian Corridor. Directly accelerator mass spectrometry radiocarbon ((14)C)-dated to 34,000–36,000 (14)C years B.P., the Oase 1 mandible is the oldest definite early modern human specimen in Europe and provides perspectives on the emergence and evolution of early modern humans in the northwestern Old World. The moderately long Oase 1 mandible exhibits a prominent tuber symphyseos and overall proportions that place it close to earlier Upper Paleolithic European specimens. Its symmetrical mandibular incisure, medially placed condyle, small superior medial pterygoid tubercle, mesial mental foramen, and narrow corpus place it closer to early modern humans among Late Pleistocene humans. However, its cross-sectional symphyseal orientation is intermediate between late archaic and early modern humans, the ramus is exceptionally wide, and the molars become progressively larger distally with exceptionally large third molars. The molar crowns lack derived Neandertal features but are otherwise morphologically undiagnostic. However, it has unilateral mandibular foramen lingular bridging, an apparently derived Neandertal feature. It therefore presents a mosaic of archaic, early modern human and possibly Neandertal morphological features, emphasizing both the complex population dynamics of modern human dispersal into Europe and the subsequent morphological evolution of European early modern humans.